Early Discussion of Breast Density and Supplemental Breast Cancer Screening: Is it Possible?. Issue 3 (2nd April 2014) - Cohen, Stuart L.; Margolies, Laurie R.; Schwager, Steven J.; Zuckerman, Samantha; Patel, Neesha; Szabo, Janet; Sonnenblick, Emily
Abstract The purpose of this study is to determine whether it is possible to make breast cancer screening more efficient in those with dense breasts. Over 12 states require that patients with dense breasts receive notification about their breast density in lay letters that are sent after the screening mammogram. Some of these letters advise patients to speak with their primary care providers about the possibility of supplemental breast cancer screening. We sought to determine whether primary care providers can discuss breast density and recommend supplemental breast cancer screening using the density of the previous mammography. This would reduce the burden of additional appointments and might increase the number of patients choosing to have supplemental screening. The mammographic breast density of 250 consecutive patients from May 2011 to September 2011 was compared with the immediate prior mammogram. Patients whose prior mammograms were more than 36 months prior or less than 8 months prior to the current exam were excluded, leaving 217 patients. The proportion of patients with breast density change was analyzed. The concordance of breast density between the two exams was assessed and the effects of patient age and the length of time between mammograms were examined. The breast density of the current and most recent prior mammogram was stable for 86.6% of patients. Neither age nor length of time between mammograms affected concordance. Primary care providers can decrease the need for multiple appointments and decrease patient anxiety by discussing breast density and screening choices prior to the patient's screening mammography. The great majority of patients will receive the correct information about their breast density by using a prior report.